Some Reflections on the Judicial Function at the Appellate Level - Harold R. Medina (Washington University Law Quarterly, 1961)
Ten years ago, and shortly before I took my seat beside my brothers of the United States Court of Appeals for the Second Circuit, I made a little speech at the annual dinner of the American Bar Association Section of Judicial Administration in honor of the Judiciary of the United States. The title of the address was “Some Reflections on the Judicial Function.” When my old friend Jim Douglas asked me to come here today to address this distinguished gathering, he suggested that I pursue the same subject, and so I shall. But, since I thought it best to have a change of scene, we shall discuss the judicial function at the appellate level.
Keywords: Judges